Association of vitamin D3 with psoriasis and psoriatic arthritis-an observational study - Mukherjee, Dibyendu; Nandi, Suman; Naiya, Suman; Imam, Parvez Wasif; Karmakar, Amit; Roy, Madhurima; Paul, Nayan (International Journal of Research in Medical Sciences, 2023)
Background: The objective of this study is to investigate the association between 25 (OH) vit D3 level and psoriasis, in our city with long sunny weather, in an attempt to clarify the controversies. Methods: The 100 patients with psoriasis including 29 with psoriatic arthritis were taken randomly as cases from medicine outpatient department of KPCMCH. Psoriasis area and severity index (PASI) was calculated for all patients with psoriasis and disease activity score (DAS28-CRP) in all arthritis patients. The control group had 150 age and sex-matched participants without any symptoms related to psoriasis or psoriatic arthritis. The 25 (OH) vit D3 serum level was estimated for both groups. This is an observational, cross-sectional study. Results: Out of total 100 patients, 55% were male and 45% female, with mean age and disease duration 49.7±6.7 years and 11.4±3.5 years, respectively. The control group had 150 subjects (86 males, 64 females). The 25 (OH) vit D3 levels of both patients and controls were 19.2±8.5 ng/ml and 29.9±6.7 ng/ml, respectively and the difference was statistically significant (p<0.05). The 25(OH) vit D3 levels were 21.9±4.1 ng/ml in patients with disease duration <10 years, and 15.9±4.2 ng/ml in patients with disease duration ≥ 10 years and difference was statistically significant (p<0.05). It was 18.9±7.8 ng/ml and 20.1±8.4 ng/ml respectively in psoriasis patients with and without arthritis but the difference was statistically not significant (p>0.05). The 25(OH) vit D3 level was lower in psoriasis with high PASI compared to psoriasis with low-moderate PASI and lower in psoriatic arthritis with high disease activity compared to arthritis with low-moderate disease activity. Conclusions: Both psoriasis and psoriatic arthritis patients had lower 25 (OH) vit D3 levels. The disease durations were directly related to 25 (OH) vit D3 insufficiency. Lower levels were associated with higher active diseases.